The Rocky Mountain population of the western Canada goose : its distribution, habitats, and management - Krohn, William B.; Bizeau, Elwood G., joint author.; U.S. Fish and Wildlife Service. (Washington, D.C. : U.S. Dept. of the Interior, Fish and Wildlife Service, 1980)
Bibliography: p. 55-57. Mode of access: Internet.